Bargaining over Time Allocation Economic Modeling and Econometric Investigation of Time Use within Families - Beblo, Miriam (Physica-Verlag HD, 2001)
In this book, time use behavior within households is modeled as the outcome of a bargaining process between family members who bargain over household resource allocation and the intrafamily distribution of welfare. In view of trends such as rising female employment along with falling fertility rates and increasing divorce rates, a strategic aspect of female employment is analyzed in a dynamic family bargaining framework. The division of housework between spouses and the observed leisure differential between women and men are investigated within non-cooperative bargaining settings. The models developed are tested empirically using data from the German Socio-Economic Panel and the German Time Budget Survey
Keywords: Population Economics; Econometrics; Population; Familie; Zeiteinteilung; Verhandlungstheorie; Mikroökonomisches Modell; Zeitallokation; Hochschulschrift